Perspectives in animal ecology and reproduction - Gupta, V. K. (Vijay Kumar), 1953-; Verma, Anil K.; Singh, G.D. (Delhi : Daya Pub. House, 2013)
Contributed articles with reference to animal species found in India.
Vol. 5-9: editors, V. K. Gupta, Anil K. Verma.
Vol. 9: editors, V.K. Gupta, Anil K. Verma, G.D. Singh.
Includes bibliographical references and index.
Keywords: Animal ecology -- India; Reproduction